Enhancing Capacity of Financial and Management Unit (UPKu) in Coastal Community Empowerment Program (P2MPP) - Lastiti Veri Anggaini, Niken (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Generally, Financial and Business Management Unit (UPKu) is an unit based on local economic empowerment management that partner with village government. The research aims to describe and analyze the capacity building strategy of Financial and Management Unit (UPKu). The study applied interactive model of data analysis from Seidel. The result of the study showed that the strategy to gain capacity of UPKu conducted through three ways, namely human resource development, rural potential development and infrastructure development. Result of research showed that inadequate of fund and capacity of human resources that still low are the problems faced in implementation the strategy.